Information-augmented building information models (BIM) to inform facilities management (FM) guidelines - Sadeghi, Marjan, author; Grigg, Neil, advisor; Elliot, Jonathan W., advisor; Mehany, Mohammed S. Hashem M., committee member; Anderson, Charles W., committee member (Colorado State University. Libraries, 2019)
The asset portfolios of Higher Education Institutions (HEI) typically incorporate a highly diverse collection of buildings with various and often shared campus uses. These facilities are typically at different points in their operational lifecycle, have different characteristics, rehabilitation cost, maintenance costs, and mission criticality. In the resource-constrained context of higher education Facilities Management (FM), building data for all facilities needs to be integrated within a highly-informed decision-making process to promote efficient operation. Further, efficient building FM workflows depend upon accurate, reliable, and timely information for various building-specific systems, components, and elements. Traditional Facilities Information Management (FIM) platforms and processes have been shown to be inefficient and limited for capturing and delivering the extensive and comprehensive data needed for FM decision making. Such inefficiencies include, but are not limited to, information loss, inconsistencies of the available data, and manual data re-entry at construction-to-operation handover and project close out. Building Information Models (BIMs) are capable of integrating large quantities of data and have been recognized as a compelling tool for facility life-cycle information management. BIMs provide an object-oriented, parametric, 3D environment where meaningful objects with intelligent behavior can contain geometric and non-geometric data. This capability makes BIMs a powerful tool for use beyond building visualization. Furthermore, BIM authoring tools are capable of automatically integrating data with FM technologies. Although BIMs have the potential to provide a compelling tool to capture, deliver, validate, retrieve, exchange, and analyze facility lifecycle information, implementation of BIMs for FM handover and integration within the context of FIM remains limited. A plethora of academic and industry efforts strive to address various aspects of BIM interoperability for handing over building data for implementation in post-construction building operation workflows. Attempts to incorporate BIMs in FIM have generally focused on one of five domains; what information is to be exchanged, how, when, by whom, and why. This three-manuscript dissertation explores FM handover information exchange scenarios and provides a comprehensive, object-oriented BIM solution that identifies the requirements for model content for FM- specific needs. The results formalize an appropriate process and structured framework to deliver BIM content using FM-specific terminologies and taxonomies. BIMs created for design and construction using this framework provide a suitable 3D resource for post-handover FM and building operation. The BIM development framework presented herein can facilitate automated model data validation at project close out and the exchange of AEC data with FIM systems. This modeling process can reduce the need for manual data re-entry or interpretation by FM stakeholders during building operation. This study defines requirements for model Exchange Objects (EOs) to meet FM data Exchange Requirements (ERs) in conjunction with the established Industry Foundation Classes (IFC). The ERs, retrieved from closeout deliverables, are mapped to appropriate IFC Model View Definition (MVD) concepts for EOs, which ultimately provide the technical solution for the FM handover exchange scenario. These concepts determine required entities, their relationships, and properties. The author further translated the concepts to the ERs of Level of Development (LOD) definitions to provide the means for an owner to formalize conveyance of geometric requirements. To formalize a BIMs semantic requirements, not addressed in the LOD schema, this study introduces Level of Semantics (LOS) by mapping ERs to IFC categories and their respective property definitions. The results also include development of an implementation agreement, which customizes the FM handover IFC Model View (MV) according to an organization's specific needs. The IFC MV implementation agreement establishes a common understanding of the FM handover MV content in alliance with the buildingSMART Data Dictionary (bsDD) schema. The modularized and repeatable nature of the resulting framework facilitates its implementation to convey FIM data exchange requirements for future projects.
Keywords: building information modeling; industry foundation classes; level of semantics; facilities management; BIM execution plan; level of development